Cooperative effect of displacement damage and inert gas impurities on deuterium retention in austenitic and ferritic-martensitic steels - Karpov, S.A.; Kopanets, I.E.; Ruzhytskyi, V.V.; Sungurov, B.S.; Tolstolutskaya, G.D. (Вопросы атомной науки и техники, 2014)
The behaviour of hydrogen (deuterium) in austenitic 18Cr10NiTi stainless steel and ferritic/martensitic steels EP-450 and EI-852 were investigated. Energetic heavy-ion irradiation has been used for modeling defect cluster formation under displacement cascade conditions to simulate nuclear-power environments. The influence of preimplanted argon on deuterium trapping in steels was studied using methods of ion implantation, the nuclear reactions D(³He,p)⁴He, thermal desorption spectrometry and transmission electron microcopy. It was found that retention of deuterium in steels is strongly enhanced by presence of radiation damages created by argon ions irradiation. The hydrogen release temperature interval shifts on 200 K to higher temperature. For the obtaining of deuterium trapping and desorption thermodynamic parameters in steels numerical simulation on the base of the continuum rate-theory was used. Изучено поведение водорода (дейтерия) в аустенитной нержавеющей стали Х18Н10Т и ферритномартенситных сталях ЕР-450 и ЕI-852. Для моделирования дефектной структуры, которая образуется в материалах ядерных энергетических установок, использовали облучение сталей высокоэнергетичными ионами аргона. Влияние предварительного облучение аргоном на удержание дейтерия в сталях исследовали методами ионной имплантации, ядерных реакций D(³He,p)⁴He, термодесорбционной спектроскопии и просвечивающей электронной микроскопии. Было установлено, что удержание дейтерия в сталях существенно повышается в присутствии радиационных повреждений, созданных предварительной имплантацией ионов аргона. Наблюдается сдвиг температурного интервала выхода водорода из кристаллической решетки на 200 К в область более высоких температур. Для извлечения термодинамических параметров захвата и десорбции дейтерия из сталей использовалась расчетная модель, основанная на теории диффузии атомов водорода в поле радиационных дефектов. Вивчено поведінку водню (дейтерію) в аустенітній нержавіючій сталі Х18Н10Т і феритно-мартенситних сталях ЕР-450 і ЕI-852. Для моделювання дефектної структури, що виникає в матеріалах ядерних енергетичних установок, використовували опромінення сталей високоенергетичними іонами аргону. Вплив попереднього опромінення аргоном на утримання дейтерію в сталях досліджували методами іонної імплантації, ядерних реакцій D(³He,p)⁴He, термодесорбційної спектроскопії та просвічуючої електронної мікроскопії. Було встановлено, що утримання дейтерію в сталях істотно зростає в присутності радіаційних пошкоджень, створених попередньою імплантацією іонів аргону. Спостерігається зміщення температурного інтервалу виходу водню з кристалічної решітки на 200 К в область більш високих температур. Для отримання термодинамічних параметрів захоплення і десорбції дейтерію із сталей використовувалася розрахункова модель, заснована на теорії дифузії атомів водню в полі радіаційних дефектів.